Tim-4 expressing monocytes as a novel indicator to assess disease activity and severity of ulcerative colitis - Xue, Guohui; Hua, Lin; Liu, Dongsheng; Zhong, Meijun; Chen, Yuanwang; Zhou, Bin; Xie, Yong; Li, Junming (Life sciences (1973), 2021)
The dysregulation of the immune response has been shown to be involved in ulcerative colitis (UC) pathogenesis. Tim-4 is a potential regulator of the immune system which plays key roles in multiple autoimmune diseases. However, whether it is involved in UC remains unclear. The aim of this research was to determine the expression of Tim-4 on circulating monocytes and its clinical significance in UC patients. In total, 36 UC patients and 34 healthy controls (HCs) were enrolled in this study. The frequencies of CD14+Tim-4+ cells, regulatory T cells (Treg) and CD14+HLA-DR−/low myeloid-derived suppressor cells (MDSCs) in the peripheral blood were determined by flow cytometry. Serum IL-6 levels were determined by chemiluminescence immunoassay. The percentage of CD14+Tim-4+ cells was higher in UC patients than in HCs. The frequency of Treg cells was significantly decreased, while that of MDSCs was significantly increased in UC patients. The frequency of CD14+Tim-4+ cells was significantly elevated in subjects with high severity, high number of defecations per day, high UC disease activity index Mayo score, high IgG, and high levels of inflammatory markers. And the percentages of Tim-4-expressing monocytes were significantly decreased in UC patients that received a 3-week treatment with mesalazine. Furthermore, the frequency of CD14+Tim-4+ cells was also positively correlated with MDSCs and negatively correlated with Treg cells. CD14+Tim-4+ cells was elevated in UC patients and could be a novel indicator to assess disease severity and activity of UC. •Tim-4 may play a role in the immune imbalance of ulcerative colitis (UC).•Frequency of Tim-4-expressing monocytes was elevated in UC patients.•Frequency of Tim-4-expressing monocytes might serve as a novel indicator to assess disease activity and severity of UC.